Design Rules for Oxygen Evolution Catalysis at Porous Iron Oxide Electrodes: A 1000‐Fold Current Density Increase. Issue 18 (6th September 2017) - Haschke, Sandra; Pankin, Dmitrii; Petrov, Yuri; Bochmann, Sebastian; Manshina, Alina; Bachmann, Julien
Abstract: Nanotubular iron(III) oxide electrodes are optimized for catalytic efficiency in the water oxidation reaction at neutral pH. The nanostructured electrodes are prepared from anodic alumina templates, which are coated with Fe2 O3 by atomic layer deposition. Scanning helium ion microscopy, X‐ray diffraction, and Raman spectroscopy are used to characterize the morphologies and phases of samples submitted to various treatments. These methods demonstrate the contrasting effects of thermal annealing and electrochemical treatment. The electrochemical performances of the corresponding electrodes under dark conditions are quantified by steady‐state electrolysis and electrochemical impedance spectroscopy. A rough and amorphous Fe2 O3 with phosphate incorporation is critical for the optimization of the water oxidation reaction. For the ideal pore length of 17 μm, the maximum catalytic turnover is reached with an effective current density of 140 μA cm −2 at an applied overpotential of 0.49 V. Abstract : Rough it up : The efficiency of iron oxide electrodes for electrochemical water oxidation at neutral pH is optimized by macropore structuration, surface roughening, and phosphate incorporation. We use anodic alumina as a macroporous template, atomic layer deposition to coat the pore walls, and electrochemical treatments to increase the surface roughness and incorporate phosphate.